Effect of dietary condensed tannins on lamb intramuscular fatty acids - Vasta V.; Lanza M.; Pennisi P.; Bella M.; Priolo A. (Advanced nutrition and feeding strategies to improve sheep and goat, 2007)
Carob pulp is a source of condensed tannins (CT), molecules able to form complexes with proteins and to inhibit ruminal microorganisms, responsible for dietary fatty acid bio-hydrogenation. The purpose of the present study was to investigate how condensed tannins from carob pulp affect intramuscular fatty acid composition in lamb longissimus dorsi muscle. Eighteen Comisana male lambs, weaned at the age of 60 days, were randomly assigned to one of two treatments: carob lambs (nine animals) were fed a diet based on carob pulp (45% as fed basis), while the remaining nine animals (PEG group) received the same diet as the carob lambs supplemented with polyethylene glycol (PEG, 42 g/kg of diet). Lambs were slaughtered at the age of 105 days. Lower amounts of conjugated linoleic acid (CLA), trans vaccenic acid (t11C18:1) (P<0.0005) and linolenic acid (C18:3n-3) (P<0.05) were found in animals fed the carob diet than in lambs fed the same diet supplemented with PEG, while arachidonic acid was found at a higher level in the carob group compared to PEG lambs (P<0.05). The CLA/t11C18:1 ratio was lower in intramuscular fat of PEG lambs (P<0.05) compared to the carob group, while no significant differences were found in total saturated-, mono- and poly-unsaturated fatty acids between treatments. Results suggest that the presence of condensed tannins in carob diet reduces ruminal bio-hydrogenation.
11. Seminar of the FAO-CIHEAM Sub-Network on Sheep and Goat Nutrition, 2005/09/08-10, Catania (Italy)